(untitled) (Global Journal of Medical Research, 2021)
Global data on Covid-19 pandemic morbidity mortality from most of the rich and poor countries has baffled public healthcare professionals Pathogenic mechanism of SARS-CoV-2 virus is still not clear even after about a year of pandemic sweeping the whole globe and killing more than 1 9 million deaths till writing of paper 08 January 2021 Socioeconomic status of populations seems to have played a vital role for the huge differences in mortality among various countries It is strange that despite extremely unhygienic local environments disadvantaged population fared much better in the Covid-19 pandemic in poor countries compared to the populations in developed countries having great healthcare infrastructure with the only exception being Japan All circumstantial evidence points towards the difference in salts natural or processed consumed Natural salts have many trace elements including radioactive elements Radioactive radiations are known to inactivate pathogens